Checkmate: Chess Artifacts and Artworks Made and Played in Extremis - Perry, Rachel (Holocaust and genocide studies, 2023)
A game of war, chess was played and pictured in a time of war by men and women, Jews and non-Jews in hiding, in the ghettos, and even behind the barbed wire of the transit, concentration, and extermination camps across Nazi-occupied Europe. Throughout the Second World War, instead of "throwing the game" and giving up, victims of National Socialism devised ingenious ways to improvise chess sets out of found materials and detritus—carved wood, folded paper, etched tin, and modeled bread. They also drew and painted chess games to document and allegorize their lives in extremis. Through a close reading of chess artifacts and artworks, this article reveals how access to materials and time, status within camp hierarchies, ethnic and national identities, and wartime experiences impacted the various ways these groups used the game of chess under difficult playing conditions. Insisting upon the central role of creativity and play, it argues that both material artifacts and artwork inform our knowledge of how individuals living under Nazi oppression thought and felt.